2022
DOI: 10.3390/nu14102002
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Chronic Kidney Disease on Nutritional Status and Its Possible Relation with Oral Diseases

Abstract: Several studies have demonstrated a strong relation between periodontal diseases and chronic kidney disease (CKD). The main mechanisms at the base of this link are malnutrition, vitamin dysregulation, especially of B-group vitamins and of C and D vitamins, oxidative stress, metabolic acidosis and low-grade inflammation. In particular, in hemodialysis (HD) adult patients, an impairment of nutritional status has been observed, induced not only by the HD procedures themselves, but also due to numerous CKD-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 201 publications
(225 reference statements)
0
14
0
Order By: Relevance
“…Metabolic acidosis is yet another homeostatic imbalance associated to renal disease: usually high anion gap acidosis, due to accumulation of phosphate and sulphate containing acids, is found, but hyperchloremic acidosis due to tubular dysfunction might also contribute; significant acidosis becomes prevalent in stage 4 CKD and is constant in dialysis patients. Long-standing acidosis is known to cause bone loss and might contribute via decreased support of alveolar bone to PO [119].…”
Section: Metabolic and Homeostatic Changes In Ckd And Their Influence...mentioning
confidence: 99%
“…Metabolic acidosis is yet another homeostatic imbalance associated to renal disease: usually high anion gap acidosis, due to accumulation of phosphate and sulphate containing acids, is found, but hyperchloremic acidosis due to tubular dysfunction might also contribute; significant acidosis becomes prevalent in stage 4 CKD and is constant in dialysis patients. Long-standing acidosis is known to cause bone loss and might contribute via decreased support of alveolar bone to PO [119].…”
Section: Metabolic and Homeostatic Changes In Ckd And Their Influence...mentioning
confidence: 99%
“…All of these protein receptors share the same molecular structure, composed of six regions of the transmembrane, forming a non-specific ionic channel [ 14 ]. TRPV1 is the first member of the TRPV subfamily that was discovered by Caterina et al in 1997 [ 15 ]. The authors cloned a receptor that can be activated by Capsaicin, thus, TRPV1 is also known as “Capsaicin receptor” [ 18 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In several clinical studies, the use of Capsaicin has been evaluated in oral rinse formulations with concentrations ranging from 0.025% to 0.075% [ 15 ]. The treatment showed good efficacy, improving BMS symptoms after only 7-day treatment with Capsaicin rinsing.…”
Section: Effects Of Capsicum Annuum L In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Several studies have demonstrated the interaction between periodontitis, diabetes, and chronic kidney disease. [20][21][22][23][24][25] When hyperglycemia, renal injury, and periodontitis coexist, increased inflammatory cytokines, enhanced insulin resistance, and the degree of periodontal inflammation in diabetic patients directly impact glycemic control and the progression of diabetic nephropathy. [26][27][28][29] However, due to the chronic nature of both diseases, influenced by multiple factors and shared risk factors, the precise mechanisms underlying their association remain uncertain.…”
Section: Introductionmentioning
confidence: 99%